Using [18F]Fluorothymidine Imaged With Positron Emission Tomography to Quantify and Reduce Hematologic Toxicity Due to Chemoradiation Therapy for Pelvic Cancer Patients - McGuire, Sarah M.; Bhatia, Sudershan K.; Sun, Wenqing; Jacobson, Geraldine M.; Menda, Yusuf; Ponto, Laura L.; Smith, Brian J.; Gross, Brandie A.; Bayouth, John E.; Sunderland, John J.; Graham, Michael M.; Buatti, John M. (International journal of radiation oncology, biology, physics, 2016)
The purpose of the present prospective clinical trial was to determine the efficacy of [18F]fluorothymidine (FLT)-identified active bone marrow sparing for pelvic cancer patients by correlating the FLT uptake change during and after chemoradiation therapy with hematologic toxicity. Simulation FLT positron emission tomography (PET) images were used to spare pelvic bone marrow using intensity modulated radiation therapy (IMRT BMS) for 32 patients with pelvic cancer. FLT PET scans taken during chemoradiation therapy after 1 and 2 weeks and 30 days and 1 year after completion of chemoradiation therapy were used to evaluate the acute and chronic dose response of pelvic bone marrow. Complete blood counts were recorded at each imaging point to correlate the FLT uptake change with systemic hematologic toxicity. IMRT BMS plans significantly reduced the dose to the pelvic regions identified with FLT uptake compared with control IMRT plans (P<.001, paired t test). Radiation doses of 4 Gy caused an ∼50% decrease in FLT uptake in the pelvic bone marrow after either 1 or 2 weeks of chemoradiation therapy. Additionally, subjects with more FLT-identified bone marrow exposed to ≥4 Gy after 1 week developed grade 2 leukopenia sooner than subjects with less marrow exposed to ≥4 Gy (P<.05, Cox regression analysis). Apparent bone marrow recovery at 30 days after therapy was not maintained 1 year after chemotherapy. The FLT uptake in the pelvic bone marrow regions that received >35 Gy was 18.8% ± 1.8% greater at 30 days after therapy than at 1 year after therapy. The white blood cell, platelet, lymphocyte, and neutrophil counts at 1 year after therapy were all lower than the pretherapy levels (P<.05, paired t test). IMRT BMS plans reduced the dose to FLT-identified pelvic bone marrow for pelvic cancer patients. However, reducing hematologic toxicity is challenging owing to the acute radiation sensitivity (∼4 Gy) and chronic suppression of activity in bone marrow receiving radiation doses >35 Gy, as measured by the FLT uptake change correlated with the complete blood cell counts.